Yield of whole exome sequencing in undiagnosed patients facing insurance coverage barriers to genetic testing. Issue 6 (3rd September 2019) - Reuter, Chloe M.; Kohler, Jennefer N.; Bonner, Devon; Zastrow, Diane; Fernandez, Liliana; Dries, Annika; Marwaha, Shruti; Davidson, Jean; Brokamp, Elly; Herzog, Matthew; Hong, Joyce; Macnamara, Ellen; et al.
Abstract: Background: Despite growing evidence of diagnostic yield and clinical utility of whole exome sequencing (WES) in patients with undiagnosed diseases, there remain significant cost and reimbursement barriers limiting access to such testing. The diagnostic yield and resulting clinical actions of WES for patients who previously faced insurance coverage barriers have not yet been explored. Methods: We performed a retrospective descriptive analysis of clinical WES outcomes for patients facing insurance coverage barriers prior to clinical WES and who subsequently enrolled in the Undiagnosed Diseases Network (UDN). Clinical WES was completed as a result of participation in the UDN. Payer type, molecular diagnostic yield, and resulting clinical actions were evaluated. Results: Sixty‐six patients in the UDN faced insurance coverage barriers to WES at the time of enrollment (67% public payer, 26% private payer). Forty‐two of 66 (64%) received insurance denial for clinician‐ordered WES, 19/66 (29%) had health insurance through a payer known not to cover WES, and 5/66 (8%) had previous payer denial of other genetic tests. Clinical WES results yielded a molecular diagnosis in 23 of 66 patients (35% [78% pediatric, 65% neurologic indication]). Molecular diagnosis resulted in clinical actions in 14 of 23 patients (61%). Conclusions: These data demonstrate that a substantial proportion of patients who encountered insurance coverage barriers to WES had a clinically actionable molecular diagnosis, supporting the notion that WES has value as a covered benefit for patients who remain undiagnosed despite objective clinical findings. CLINICAL TRIAL REGISTRATION: NCT02450851. Registered 19 May 2015.